IMPROVEMENT OF PHYSIOLOGICAL CONDITION AND LATEX FLOW OF RUBBER CLONES AFFECTED BY TAPPING PANEL DRYNESS IN RESPONSE TO COMBINATION NAPHTHALENE ACETIC ACID, ASCORBIC ACID, AND NUTRITION TREATMENTS - Ade Fipriani Lubis; Radite Tistama (Jurnal Penelitian Karet, 2021)
The TPD incident is one of the factors causing rubber estates to lose their production. The objective of this research was to arrange formulation for recovering of tapping panel dryness (TPD) chases, especially on PB 260 and IRR 42 clones. The experiment was divided into two experiments, that were arranged into a split plot design with two treatment factors, first the main plots of rubber plant clones (PB 260 and IRR 42), and second different NAA concentrations in the step 1. The best combination of the first experiment was added with different concentrations of ascorbic acid in the research experiment II. The physiological variables observed were sucrose, inorganic phosphate, thiol, latex production, and biochemical variables were SOD, APX, and POD enzyme activities. The TPD-affected plant could produce latex under treatment of NAA and nutrient for six months NAA 10 ppm treatment significantly affected on Pi content and had positive effect on latex production. Treatment of ascorbic acid also increased production in rubber plants and affected on POD and SOD activities. There were differences respond between high metabolism clone PB 260 and low metabolism clone IRR 42 to combination of NAA, nutrient, and ascorbic acid treatment.